Gender differences in physical activity following acute myocardial infarction in adults: A prospective, observational study. (29th August 2020) - Minges, Karl E; Strait, Kelly M; Owen, Neville; Dunstan, David W; Camhi, Sarah M; Lichtman, Judith; Geda, Mary; Dreyer, Rachel P; Bueno, Héctor; Beltrame, John F; Curtis, Jeptha P; Krumholz, Harlan M
Abstract: Aims: Despite the benefits of regular physical activity participation following acute myocardial infarction, little is known about gender differences in physical activity among patients after acute myocardial infarction. We described, by gender, physical activity trajectories pre- and post-acute myocardial infarction, and determined whether gender was independently associated with physical activity. Methods and results: The Variation in Recovery: Role of Gender on Outcomes of Young AMI patients (VIRGO) study, conducted at 103 US, 24 Spanish, and three Australian hospitals, was designed, in part, to evaluate gender differences in lifestyle behaviors following acute myocardial infarction. We used baseline, one-month, and 12-month data collected from patients aged 18–55 years ( n  = 3572). Patients were assigned to American Heart Association-defined levels of physical activity. A generalized estimating equation model was used to account for repeated measures within the same individual over time. Men were more active (≥150 min/wk moderate or ≥75 min/wk vigorous activity) than women at baseline (42% vs 34%), one month (45% vs 34%), and 12 months (48% vs 36%) (all p  < 0.0001). Men engaged in a significantly longer duration of activity at each time point. When controlling for all other factors, women had 1.37 times the odds of being less active than men from pre-acute myocardial infarction to 12-months post-acute myocardial infarction (95% confidence interval: 1.21–1.55). Non-white race, non-active workplaces, smoking, diabetes, hypertension, and obesity were also associated independently with being less active over time (all p  < 0.05). Conclusions: Although activity increased modestly over time, women recovering from acute myocardial infarction were less likely to meet physical activity recommendations than were men. By identifying factors associated with low levels of activity during acute myocardial infarction recovery, targeted interventions can be introduced prior to hospital discharge.